Decorating electron redundant SinAl12–nN12 (n = 1, 2) nanocages with superalkalis M3O (M = Li, Na, K): excess electron D-A frameworks and nonlinear optical properties. (19th May 2021) - Li, Yuhong; Ruan, Mingyue; Chen, Hongshan
Abstract : The electron redundant Si n Al12– n N12 ( n  = 1, 2) nanocages decorated with superalkalis M3 O (M = Li, Na, K) are designed and their stabilities, electronic structures and nonlinear optical (NLO) properties are investigated by using density functional theory calculations. The Si-doped Si n Al12– n N12 cages are more stable than the stoichiometric Al12 N12, and the calculation reveals that superalkalis M3 O can be bound strongly on these electron redundant cages, with binding energies about 5 eV. The superalkalis M3 O transfer electrons to Si n Al12– n N12 and the M3 O@Si n Al12– n N12 form excess electron donor–acceptor (eeD-A) frameworks. The excess electrons in M3 O@Si n Al12– n N12 form loosely bound lone pair electrons, which push up the HOMO energies and lead to narrower energy gaps. The special electronic structures make these complexes have high NLO responses and they are nearly transparent in deep-ultraviolet region. The largest first hyperpolarisability is observed for K3 O@Si2 Al10 N12 and the value reaches 7.12 × 10 5 au. We hope this study can provide new strategies for exploring unconventional NLO materials. GRAPHICAL ABSTRACT: